ISLAMIC VALUES FROM THE WORK OF BUILDING CULTURE OF KARATON YOGYAKARTA - Erma Yusmi (Sunan Kalijaga International Journal on Islamic Educational Research, 2019)
Karaton Yogyakarta has Islamic Values or can be called Islam as the official religion of Karaton which includes spiritual activities and physical activities that can’t be separented from symbolic meaning. The results of architectural works in the from of buildings which are historical relics of Karaton Yogyakarta need to be preserved. Preserved not only in the form of cultural form, but also related to Islamic values contained in the form of these objects. The result of this study indicate that, in the cultural work of the building of the Karaton Yogyakarta there are aspects of Islamic values, which is the aspect of the value of ilahiyyah (human relationship with God) and the value of insaniyyah (human relationship with fellow beings) is seen in the shape of the building. Such as the shape of the Yogyakarta Monument building as well as the form of the Ghede Kauman mosque. From the work of building culture has meaning in the aspect of ilahiyyah value, that human beings are commanded to always remember and carry out the command of Allah to be human beings to Allah almighty. And the aspect of insaniyyah value, that doing good and benefiting fellow humans is therefore one form of taqwa to Allah Almighty.